Writing Instruction Using Growth Mindset Training and Process-Genre Approach to Enhance Academic Writing Abilities of Upper Secondary Students - Nutan, Pannawat; Wongsuwan Kongpao, Wipawan (An Online Journal of Education, 2026)
The objectives of this study were: 1) to compare the academic writing ability of an experimental group before and after using the combination of growth mindset training and process-genre approach, and 2) to compare the post-instruction academic writing ability between the experimental and control groups. The participants were 60 12th-grade students, selected through multistage random sampling and equally divided into an experimental group and a control group of 30 students each. The research instruments included: 1) three lesson plan units with an index of Item-Objective Congruence (IOC) of 0.92, 2) an academic writing ability test using an analytic scoring rubric, having an IOC of 0.94 and a Cronbach’s alpha reliability coefficient of 0.95, and 3) a post-writing reflection form with an IOC of 0.70. Quantitative data were analyzed using paired-samples t-test to compare the pre-test and post-test scores of the experimental group, and independent t-test to compare the post-test scores between the experimental and control groups. Qualitative data were analyzed through content analysis. The quantitative findings revealed that: 1) the mean post-test score of the experimental group was significantly higher than its pre-test score at the .01 level (M = 89.73, SD = 7.89), and 2) the experimental group significantly outperformed the control group on the post-test at the .01 level of significance (M = 89.73, SD = 7.89).